2004
DOI: 10.1007/s00467-004-1618-6
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine therapy monitored with abbreviated area under curve in nephrotic syndrome

Abstract: Cyclosporin A (CsA) is an effective therapy for children with long-lasting nephrotic syndrome (NS). Long-term treatment can result in chronic CsA nephropathy (CsAN) and there is controversy concerning its incidence and severity. Trough levels are commonly used to monitor the drug concentration. We report a retrospective clinical and histological analysis of 18 children (12 males, 6 females) with steroid-dependent nephrotic syndrome (15 patients) and partially steroid-sensitive nephrotic syndrome (3 patients) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
11
0
2
Order By: Relevance
“…Numerous studies have documented the prevalence of CsAN in patients who were treated for idiopathic nephrotic syndrome. Since 1986, Ͼ200 follow-up biopsies in patients who were treated with CsA for SDNS have been reported in the literature (1,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). These studies are difficult to compare because they vary in the number of biopsies, underlying renal pathology, duration of follow-up, dosages of CsA, and criteria to define CsAN.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented the prevalence of CsAN in patients who were treated for idiopathic nephrotic syndrome. Since 1986, Ͼ200 follow-up biopsies in patients who were treated with CsA for SDNS have been reported in the literature (1,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). These studies are difficult to compare because they vary in the number of biopsies, underlying renal pathology, duration of follow-up, dosages of CsA, and criteria to define CsAN.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] In a clinical setting, the typical practice of cyclosporine dosage adjustments is frequently used to determine its concentration and then adjust the dosage by a trial-and-error approach. However, controversy still surrounds the dosage regimen, therapeutic concentration range, and method of therapeutic drug monitoring of cyclosporine in the treatment of collagen diseases [8][9][10] ; the pharmacokinetics of cyclosporine show large variations in blood levels following its oral or intravenous administration, not only interindividually, but also intraindividually, 11) especially after oral dosing. 12) Recent studies reported low dose cyclosporine therapy, which was adjusted to gain of blood trough concentration approximate 80-150 ng/mL, was an effective and less toxic cyclosporine therapy for the regulation of connective tissue diseases with RA, 13) SLE, [14][15][16] and lupus nephritis.…”
mentioning
confidence: 99%
“…The carriage of these strains, characterized by mutations of the ftsI gene encoding the reach optimal values, both the clinical/microbiological efficacy is ensured and the emergence of resistant bacteria is hampered. 31 As a matter of fact, an almost maximal consensus (98%) has been reached on the importance of the PK/PD profile of the antibiotic of choice for the patient's treatment and to avoid an increase of microbial resistance.…”
Section: Resultsmentioning
confidence: 99%